Problems in granting land title to Sulod Bukidnon a case of Brgy. Jayobo, Lambunao, Iloilo. - Brillo, Encel Joy F.
This is a descriptive study at the same time exploratory in nature of the Sulod-Bukidnon's claim of their ancestral domain title. Manly, the researchers put emphasis on the mandate of the NCIP (National Commission on Indigenous Peoples) for the implementation of the IPRA including the requirements and processes for the granting of CADT (Certificate of Ancestral Domain Title); The Sulo-Bukidnons basis of ancestral domain claim, awareness of IPRA and NCIP, and Customary law with regards to land ownership; The factors that hinder the NCIP operations for the granting of Sulod-Bukidnon's ancestral claim; and the accomplishments of NCIP and the sulod-Bukidnon to date in the pursuit of their respective interest., It was found out in the study that any persons/community who are classified by the NCIP (based on genealogical survey), as indigenous could apply for CADT. The CADT recognizes the rights, possession and ownership of Indigenous Peoples (IPs) over their ancestral domains. According to RA 8371, IPRA, respect the indigenous concept of particular ownership of sch land. The law also recognizes that the IP's ancestral domain is a community property that belongs to all generations. NCIP on the other hand was created as the primary agency for the implementation of policies, plans, and programs to promote the rights and well being of the Ips. This two (IPRA and NCIP) actually are the support systems of the IPs on their claim to their ancestral domain title. It was also found out in the study that the indigenous people in the periphery have different notion/lack of idea regarding IPRA and NCIP, compared to the people in the center or near in the barangay proper, who are more aware of what the law and the commission was all about. The latter kind of people composed mainly of tribal leaders, who undergo a series of seminars conducted by NCIP. The IPs are the one who identify the areas covered by their ancestral domain. Basically, long-time occupancy and cultivation of land are the main condition for the ownership of the land. The NCIP on the other hand only facilitates the granting of land title to the IPs. There were several factors identified in these study that affected the granting of land title to the Sulod-Bukidnon. Mainly, conflict of interest between IPs and the other government agencies/institution, specifically, West Visayas State University - College of Agriculture and Forestry (WVSU-CAF), IPs lack of awareness about the law and the commission, and other personal interest.